Caracterização funcional da histona H2B variante em diferentes formas de vida de Trypanosoma cruzi - Roson, Juliana Nunes [UNIFESP] (2019)
The differentiation of Trypanosoma cruzi is followed by changes in parasite morphology and a complete reorganization of the nucleus and chromatin structure. Studies indicate that the deposition of histone variants changes chromatin structure, possibly affecting gene regulation. Recently, in our group it was verified that histone H2BV is enriched in the chromatin of trypomastigote forms of T. cruzi. In this dissertation, we sought to understand the role of histone H2BV in the life forms of T. cruzi. For this, heminoucautes parasites were generated for H2BV (H2BV-HtzKO) and the interaction partners of this protein were evaluated. In general, H2BV-HtzKO clones exhibit higher rates of proliferation and differentiation in metacyclics over wild-type parasites. In addition, they have a higher number of cells in the S phase of the cell cycle. By quantitative proteomics, it has been confirmed that H2BV expression is decreased in chromatin and H2BV-HtzKO parasites and, interestingly, we have found that the other histone variants (H2A.Z and H3V) are also less abundant. In addition, the abundance of other histones (namely, H4, H2A and H1) is increased in the H2BVHtzKO parasites suggesting a compensatory mechanism in histone deposition at the chromatin. Pulldown assays were performed using the H2BV and canonical H2B recombinants (as a control) to identify their specific interaction partners in the epimastigote or trypomastigote forms. Many interesting, proteins have been identified, but the bromodomain-2 factor (BDF2) is exclusively found in trypomastigote extracts. It is known that BDF2 recognizes histone acetylation and, according to the same, we find that H2BV itself is acetylated at residue K97. The study of proteins with epigenetic function as highlighted in this dissertation are important for a better understanding of the biology of trypanosomes since they participate in pathways essential for the growth / differentiation of the parasite and thus may also be excellent therapeutic prototypes for trypanosomiasis.